KARAKTERISTIK FUNGSIONAL EDIBLE FILM DARI KOMPOSIT PATI/KITOSAN/ASAM STEARAT: KARAKTERISTIK FUNGSIONAL EDIBLE FILM DARI KOMPOSIT PATI/KITOSAN/ASAM STEARAT - Ristika Oktavia Asrizaa; Shelly Victory; Shania Sakhila; Restani Eka Putri; Addela Amelia; Soluna Desbait Hutagalung (Jurnal Natural, 2021)
In this article, the author reports that the manufacture of edible films has been carried out as well as an analysis of the effect of adding starch on the functional characteristics of edible films. The stages of making bioplastics include extracting starch from empty oil palm fruit bunches, making edible plastics and material characterization. In the manufacture of bioplastics, variations in starch content are carried out to determine the most appropriate starch content in producing edible films. Based on the results of the FTIR characterization of edible films with variations in the amount of starch, it shows that the more the amount of starch added, the hydrophilic properties of the edible film will increase.